Documenting modern Sri Lanka Portuguese - Cardoso, Hugo C. (2019)
Sri Lanka Portuguese (SLP) is a Portuguese-lexified creole formed during Sri Lanka’s Portuguese colonial period, which lasted from the early 16th century to the mid-17th century. The language withstood several political changes and became an important medium of communication for a portion of the island’s population, but reached the late 20th century much reduced in its distribution and vitality, having essentially contracted to the Portuguese Burgher community of Eastern Sri Lanka. In the 1970s and 1980s, the language was the object of considerable research and documentation efforts, which were, however, curtailed by the Sri Lankan civil war. This chapter reports on the activities, challenges, and results of a recent documentation project developed in the post-war period and designed to create an appropriate and diverse record of modern SLP. The project is characterised by a highly multidisciplinary approach that combines linguistics and ethnomusicology, a strong focus on video recordings and open-access dissemination of materials through an online digital platform (Endangered Languages Archive), archival prospection to collect diachronic sources, a sociolinguistic component aimed at determining ethnolinguistic vitality with a view to delineating revitalisation strategies, and a strongly collaborative nature. This chapter describes the principal outputs of the documentation project, which, in addition to a digital corpus of transcribed and annotated materials representing modern manifestations of SLP and the oral/musical traditions of the Burghers, also include the findings of the sociolinguistic survey, an orthographic proposal for the language, as well as the copies and transcriptions of hard-to-obtain historical sources on SLP (grammars, dictionaries, biblical translations, liturgical texts, collections of songs).